Evaluation of antioxidant, total phenol and flavonoid content and antimicrobial activities of artocarpus altilis (breadfruit) of underutilized tropical fruit extracts - Jalal, Tara Kamal; Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Momand, Lailuma; Draman, Samsul; Md Isa, Muhammad Lokman; Abdull Rasad, Mohammad Syaiful Bahari; Omar, Muhammad Nor; Ibrahim, Muhammad; Abdul Wahab, Ridhwan (Springer, 2015)
Artocarpus altilis (breadfruit) pulp, peel and whole fruit were extracted with various solvents such as hexane, dichloromethane (DCM) and methanol. The antioxidant activity of these extracts were examined using the stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test. IC50 was 55 ± 5.89 μg/ml for the pulp part of methanol extract. In the β-carotene bleaching assay, the antioxidant activity was 90.02 ± 1.51 % for the positive control (Trolox) and 88.34 ± 1.31 % for the pulp part of the fruit methanol extract. The total phenolic content of the crude extracts was determined using the Folin-Ciocalteu procedure; methanol pulp part demonstrated the highest phenol content value of 781 ± 52.97 mg GAE/g of dry sample. While the total flavonoid content was determined using the aluminium chloride colorimetric assay, the highest value of 6213.33 ± 142.22 mg QE/g was indicated by pulp part of the fruit methanol extract. The antimicrobial activity of the crude extracts was tested using disc diffusion method against pathogenic microorganisms: Staphylococcus aureus, Staphylococcus epidermidis, Bacillus cereus, Salmonella typhimurium, Escherichia coli, Klebsiella pneumonia and Candida albicans. Methanol extract of pulp part was recorded to have the highest zone of inhibition against Gram-positive and Gram-negative bacteria. The minimum inhibitory concentration (MIC) and MBC/minimal fungicidal concentration (MFC) for the extracts were also determined using the microdilution method ranging from 4000 to 63 μg/ml against pathogenic microbes. The MBC/MFC values varied from 250 to 4000 μg/ml. A correlation between antioxidant activity assays, antimicrobial activity and phenolic content was established. The results shows that the various parts of A. altilis fruit extracts promising antioxidant activities have potential bioactivities due to high content of phenolic compounds.